Internal Factors of Academic Entrepreneurship: the Case of Four Malaysian Public Research Universities - Mohar Yusof; Mohammad Saeed Siddiq; Leilanie Mohd (Journal of Entrepreneurship, Management and Innovation)

(untitled)
His paper focused on academic entrepreneurship, an emerging phenomenon in Malaysian public research universities. The research demonstrated that academic entrepreneurship produced positive impact on research commercialization and university technology transfer for these public research universities. Academic entrepreneurship was also found to be one of the missing gaps in fulfilling the complete process of research and development up to commercialization. This study provided evidence of the appropriateness of using an organizational framework of academic entrepreneurship to measure the influence of the internal environment in stimulating the level of academic entrepreneurship. The results demonstrated that control systems, organizational culture, human resource management systems and entrepreneurial leadership behaviour were key predictors of academic entrepreneurship in these universities.